DETERMINANTS OF GOVERNMENT SECURITIES YIELD USING VECM - Batara Maju Simatupang (Jurnal Bisnis Manajemen, 2021)
This study aims to uncover the determinants’ effect on the return rate of government securities (GS). This study's data uses the government bonds that can be traded with the ten-year tenor, and the time-horizon of the collected data spans from 2009:M1 to 2018:M6. The study methodology utilizes the vector error correction model (VECM) model to determine the short-term backward behavior, which refers to the situation where the short-term balances are corrected for the long-term balances. Additionally, it is also to reveal the relationship between the variables within the model. Thus, this study is to see whether GS’s reciprocal level has been at the value of efficient return or not. The results show that the cointegrated determinants of the Bank Indonesia (BI) rate / seven days repo, outstanding tradable government bonds, Fitch Rating, exchange rate, sovereign country risk, and regional bond index positively affects the GS yield. In contrast, the determinants of Fitch Rating, exchange rate, sovereign country risk, and outstanding tradable government bond negatively influence GS yields. The implication of this research is that the Indonesian government securities are interdependent with the identified determinants; thus, the Indonesian government should maintain the movement of those determinants to ensure that its GS stays positive.